Solid propellant containing nickel-based energetic catalyst and its manufacturing method and application

By introducing [NI (N2H4) 3] (NO3) 2 and/or [NI (N2H4) 2] (N3) 2 as a capable catalyst in the solid pushing agent, it solves the problem of insufficient energy release during the combustion process of solid propellars , Achieve higher energy release and combustion efficiency.

CN116768691BActive Publication Date: 2025-01-24NANJING UNIV OF SCI & TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310838571.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-07-10
Publication Date
2025-01-24
Estimated Expiration
2043-07-10

AI Technical Summary

Technical Problem

The existing solid propellants are insufficient in the combustion process, making it difficult to meet the needs of higher energy release.

Method used

[Ni(N2H4)3](NO3)2 and/or [Ni(N2H4)2](N3)2 are introduced into the solid propellant as energetic catalysts to catalyze the combustion of the oxidizer.

Benefits of technology

The energy release during the combustion process of solid propellant is significantly improved, the main exothermic decomposition peak temperature is increased, and the detonation heat and combustion rate are also significantly increased, indicating that the catalyst has good catalytic performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116768691B_ABST
    Figure CN116768691B_ABST
Patent Text Reader

Abstract

The present invention discloses a solid propellant containing a nickel-based energetic catalyst and a manufacturing method and application thereof, and belongs to the field of energetic material preparation. The present invention provides an application of energetic catalysts [Ni(N2H4)3](NO3)2 and / or [Ni(N2H4)2](N3)2 in solid propellants. When the two energetic catalysts are in the solid propellant, the burning rate and the burning temperature of the solid propellant are increased, so that the energy of the solid propellant is released more fully and the combustion is more complete during the combustion process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of energetic material preparation, and more specifically, relates to a solid propellant containing a nickel-based energetic catalyst and a manufacturing method and application thereof. Background Art

[0002] As the core functional component of solid propellants, combustion catalysts can play an important role in regulating the burning rate of solid propellants, controlling energy release and plume characteristic signals. The development of combustion catalysts has evolved from traditional metal, metal oxide and metal composite oxide catalysts to composite nanocatalysts, and from inert catalysts to energetic catalysts. Energetic catalysts are generally energetic salts or complexes prepared by introducing energetic groups such as nitro or azide groups into organic metal salt catalyst molecules. Energetic catalysts not only have the catalytic effects of traditional catalysts, but can also improve the energy level of propellants and have good development prospects. Further improving the energy release during the combustion of solid propellants is a common pursuit in the field of solid propellants. Summary of the invention

[0003] 1. Problem to be solved

[0004] In order to further improve the energy release during the combustion process of solid propellants, the first aspect of the present invention provides the use of [Ni(N2H4)3](NO3)2 and / or [Ni(N2H4)2](N3)2 in solid propellants; the second aspect provides solid propellants comprising [Ni(N2H4)3](NO3)2 and / or [Ni(N2H4)2](N3)2; the third aspect provides a method for manufacturing a solid propellant comprising [Ni(N2H4)3](NO3)2 and / or [Ni(N2H4)2](N3)2.

[0005] 2. Technical solution

[0006] [application]

[0007] A first aspect of the present invention provides the use of [Ni(N2H4)3](NO3)2 (abbreviated as NHN) and / or [Ni(N2H4)2](N3)2 (abbreviated as NHA) in solid propellants.

[0008] As a preferred embodiment of any technical solution of the first aspect of the present invention, the [Ni(N2H4)3](NO3)2 and / or [Ni(N2H4)2](N3)2 is used to catalyze the combustion of the oxidizer in the solid propellant.

[0009] As a preferred embodiment of any technical solution of the first aspect of the present invention, the amount of [Ni(N2H4)3](NO3)2 and / or [Ni(N2H4)2](N3)2 added to the solid propellant is 0-5%, excluding 0.

[0010] [Solid propellant]

[0011] A second aspect of the present invention provides a solid propellant comprising an oxidant, a reductant and an energetic catalyst; the oxidant comprises ammonium perchlorate, and the energetic catalyst comprises [Ni(N2H4)3](NO3)2 and / or [Ni(N2H4)2](N3)2.

[0012] As a preferred embodiment of any technical solution of the second aspect of the present invention, the solid propellant comprises an oxidant, a reductant and an energetic catalyst; the oxidant comprises ammonium perchlorate, and the energetic catalyst comprises [Ni(N2H4)3](NO3)2.

[0013] As a preferred embodiment of any technical solution of the second aspect of the present invention, the solid propellant comprises an oxidant, a reductant and an energetic catalyst; the oxidant comprises ammonium perchlorate, and the energetic catalyst comprises [Ni(N2H4)2](N3)2.

[0014] As a preferred embodiment of any technical solution of the second aspect of the present invention, the solid propellant comprises an oxidant, a reductant and an energetic catalyst; the oxidant comprises ammonium perchlorate, and the energetic catalyst comprises [Ni(N2H4)3](NO3)2 and [Ni(N2H4)2](N3)2.

[0015] As a preferred embodiment of any technical solution of the second aspect of the present invention, the mass percentage of the oxidizer in the solid propellant is 58% to 63%, excluding 63%; the mass percentage of the energetic catalyst in the solid propellant is 0 to 5%, excluding 0.

[0016] As a preferred embodiment of any technical solution of the second aspect of the present invention, the sum of the mass percentages of the oxidant and the energetic catalyst is 63%.

[0017] As a preferred embodiment of any technical solution of the second aspect of the present invention, the reducing agent is aluminum powder, which accounts for 17% by mass of the solid propellant.

[0018] As a preferred embodiment of any technical solution of the second aspect of the present invention, it further includes an adhesive, a plasticizer and a curing agent.

[0019] As a preferred embodiment of any technical solution of the second aspect of the present invention, the adhesive includes HTPB (hydroxy-terminated polybutadiene), the plasticizer includes DOS (diisooctyl sebacate), and the curing agent includes TDI (toluene 2,4-isocyanate).

[0020] [Manufacturing method]

[0021] The third aspect of the present invention provides a method for producing the solid propellant of the second aspect of the present invention, comprising the step of mixing and stirring an oxidizer and an energetic catalyst.

[0022] As a preferred embodiment of any technical solution of the third aspect of the present invention, it specifically includes raw material drying, stirring, vacuum pouring and curing;

[0023] Raw material drying: the raw material is heated and dried in a vacuum oven for a specific time;

[0024] Stirring: Add the adhesive, oxidant, plasticizer, energetic catalyst and curing agent into the container in sequence and mix them evenly in a vacuum stirrer;

[0025] Vacuum casting: The slurry is poured into a PTFE mold and kept under high vacuum for a specific time;

[0026] Curing: The mold is placed in an oven and heated for a specific time to obtain a fully cured solid propellant.

[0027] 3. Beneficial effects

[0028] The present invention applies NHN and NHA to solid propellants for the first time to improve the energy release during the combustion of solid propellants. Studies have shown that the main exothermic decomposition peak temperature of solid propellants containing energetic catalysts NHN and NHA is significantly higher than that of solid propellants without energetic catalysts. The explosion heat of solid propellants containing NHN or NHA is higher than that of solid propellants without energetic catalysts. The combustion rate of solid propellants containing NHN or NHA is higher than that of solid propellants without energetic catalysts, indicating that NHN and NHA have good catalytic properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 The SEM images of NHN, NHA crystals and H0-H4 solid propellants;

[0030] Figure 2 is the DSC curve of H0-H4 solid propellant;

[0031] Figure 3 is the TGA curve of H0-H4 solid propellant;

[0032] Figure 4 is the density and detonation heat of H0-H4 solid propellant;

[0033] Figure 5 This is the combustion image of H0-H4 solid propellant at a pressure of 0.5MPa;

[0034] Figure 6 is the burning rate in nitrogen atmosphere at room temperature (r, mm·s -1) and pressure (P, 0.5-2.5MPa);

[0035] Figure 7 It is the combustion temperature curve of H0-H4 solid propellant at a pressure of 0.5MPa;

[0036] Figure 8 SEM images and size distribution of CCPs for solid propellants: a, H0; b, H1; c, H2; d, H3; e, particle size of H4;

[0037] Fig. 9 is the XRD spectrum of CCPs. DETAILED DESCRIPTION

[0038] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which the invention belongs; the term "and / or" used herein includes any and all combinations of one or more of the associated listed items.

[0039] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. If the manufacturers of the reagents or instruments are not specified, they are all conventional products that can be purchased commercially.

[0040] NHN and NHA were prepared according to the published literature method (patent document CN1042625C; Zhu Shunguan, Xu Dawei, Cao Shijin, Mou Jingyan, Cheng Liguo. High-powered complex detonator - nickel hydrazine [J]. Explosives, 2005 (05): 18-20.), and spheroidized to a particle size of about 50 μm; AP was provided by Nanjing Wanqing Chemical Company; micronized aluminum powder (Al) with an average diameter of ~13 μm was purchased from Anshan Iron and Steel Industry Fine Aluminum Powder Co., Ltd.; diisooctyl sebacate (DOS ≥ 97%) and toluene 2,4-isocyanate (TDI) were both from Aladdin (Shanghai, China); and terminal hydroxyl polybutadiene (HTPB) was provided by Zibo Qinglong Chemical Company. Among them, the SEM image of the NHN crystal morphology is shown in the figure below: Figure 1 shown.

[0041] 1. Propellant formula design

[0042] The propellant formula design refers to the classic standard formula design, in which the addition amount of NHN and NHA is added according to the percentage of catalyst in conventional solid propellant, and the value is 1% and 5%. The formula is shown in Table 1.

[0043] Table 1 Composition and content of propellant formula (%)

[0044]

[0045]

[0046] Note: superscript a, the contents of HTPB, DOS and TDI in all formulations are 13%, 4% and 3% respectively.

[0047] 2. Preparation of HTPB-based propellants

[0048] The preparation process of solid composite propellant mainly includes raw material drying, stirring, vacuum casting and curing. First, the raw materials were dried in a vacuum oven at 65 ° C for 72 h according to the content of each raw material in Table 1. Then, HTPB, AP, DOS, NHN or NHA, TDI (30.0 g in total) were added to the container in sequence and uniformly mixed for 20 min in ultrasound at 40 ° C. Next, the slurry was poured into a customized polytetrafluoroethylene mold (10×10×100 mm) and kept under high vacuum (1.0 Pa) for 3 hours. The mold was then placed in an oven at 65 ° C for 7 days to obtain a fully cured propellant. Finally, the cured propellant was processed into long strips (5×5×30 mm) for combustion performance testing. These strips were coated with flame retardants (polyvinyl butyral and ethanol) to obtain a flat burning surface.

[0049] 3. Scanning Electron Microscope

[0050] The raw materials and their corresponding propellant parts were characterized by Zeiss scanning electron microscopy at an accelerating voltage of ~6.5 kV and a working distance. SEM images of NHN, NHA crystals and the surface structure of the prepared HTPB-based composite propellant are shown in Figure 1 As shown in the figure, the crystal morphology of NHN and NHA is cubic, and the particle size of NHN and NHA after spheroidization is 50μm. We can also see that in the H0 sample, AP (300-350μm) and Al (~13μm) are respectively and evenly embedded in the HTPB matrix; in the H1-H4 samples, AP (300-350μm), NHN or NHA and Al (~13μm) are respectively and evenly embedded in the HTPB matrix. The prepared propellants H0-H4 have no voids and can be used to determine the burning rate and burning temperature.

[0051] 4. Thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC) analysis

[0052] In order to study the thermal behavior of HTPB-based composite propellants containing NHN and NHA, thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC) were used to investigate the thermal behavior of the propellants at 50 mL·min -1 , thermal decomposition behavior under Ar atmosphere. In the temperature range of 50-400 °C, the heating rate is 10 K·min -1 The sample mass was 1 mg.

[0053] We conducted DSC-TG experiments, in which the DSC and TGA curves are shown in Figure 2 , Figure 3 The detailed parameters are shown in Table 2. Figure 2 , Figure 3 It can be found that the thermal decomposition mass losses of H1 and H2 are 75.38% and 76.69%, respectively, which is comparable to H0, and the mass losses of H3 and H4 are 85.31% and 81.9%, respectively. These mass losses, compared with the exothermic process, indicate that there are volatile gas products, and compared with H1 and H2, H3 and H4 with the addition of NHA have further increased mass losses, which indicates that the addition of NHA can significantly improve the efficiency of thermal decomposition compared with NHN. Compared with H0, H1, H2, H3, and H4 without catalyst components, the exothermic peaks are significantly advanced by 24.9°C, 26.91°C, 29.25°C, and 32.9°C, and the exothermic peak width is significantly narrowed. This shows that both NHN and NHA have a significant promoting effect on the exothermic reaction of the composite propellant. At the same time, according to the enthalpy change of solid propellant calculated by DSC curve, it can be found that the heat release of H1, H2, H3, and H4 is significantly higher than that of H0, which also shows that the addition of NHN and NHA can effectively promote the heat release of composite solid propellant. Since NHN and NHA decompose at a temperature lower than the melting point of AP, the released heat compensates for the endothermic absorption of AP melting process, so there is no AP endothermic peak on the DSC curves of H1, H2, H3, and H4.

[0054] Table 2 DSC parameters at a heating rate of 10 K / min in Ar atmosphere

[0055]

[0056] Note: i , initial temperature of melting and decomposition, ℃; T p , peak temperatures of melting and decomposition, ΔH, and total heat release, T e , the end temperature of the reaction.

[0057] 5. Energy release and combustion performance - measurement of explosion heat

[0058] To better characterize the energy release performance of composite propellants, density and detonation heat were measured.

[0059] The detonation heat was measured with a detonation calorimeter under 3.0 MPa argon atmosphere, where the sample was ignited by an electrically heated NiCr bridge wire (Φ=0.5 mm).

[0060] like Figure 4 As shown in Figure 2, the density of solid propellants containing NHA or NHN is between 1.70 and 1.74 g cm -3 The explosive heat is between 4900-5800 J·g-1 within the range.

[0061] The density of solid propellants containing NHN and NHA is slightly higher than that of solid propellants without NHN and NHA, among which the density of H3 is 1.733 g·cm -3 , the density of H4 is 1.744 g·cm -3 The explosion heat of H3 is 5744.98 J·g -1 The explosion heat of H4 is 5446.13 J·g -1 . The detonation heat of both is 13.7% and 9.9% higher than that of H0, respectively. This result shows that NHA has an impact on the gas phase reaction during the combustion process, which increases the flame temperature and combustion efficiency, and increases the detonation heat. It is also worth noting that the detonation heat of the composite solid propellant with 1% NHA content is higher than that of the composite propellant with 5% NHA content, which shows that the increase in the detonation heat of the propellant is not only the heat release of NHA alone, but the result of the catalytic effect of NHA on the overall composite propellant. At the same time, the detonation heat of H4 is lower than that of H3, which shows that when the content of NHA increases, it has a catalytic effect on the solid propellant, resulting in insufficient energy release. Similarly, when NHN is added to the composite propellant, the detonation heat is further improved, among which the detonation heat of the H1 formula is increased by as much as 10.7%, which shows that NHN also has an excellent catalytic effect on the composite solid propellant at a content of 1%.

[0062] 6. The influence of flame propagation and pressure on burning rate

[0063] In order to study the combustion performance of the prepared solid propellant, a multifunctional combustion diagnostic system was used. The flame propagation speed was recorded by a high-speed camera (ACS-1M60) through a transparent window at a rate of 1000 frames / s.

[0064] Based on the continuous flame photos obtained by the high-speed camera and the corresponding combustion surface advancement process, the combustion rate was calculated as follows: Figure 5 The obtained burning rate values ​​have a deviation of <5%. It is obvious that the burning surface is basically progressive in a parallel manner. From the figure, it can be found that the propellant flame area after adding NHN or NHA is significantly increased and more concentrated, which indicates that NHN or NHA makes the propellant reaction more violent and increases the combustion temperature of the gas.

[0065] The relationship between the combustion rate and the pressure (0.5-2.5MPa) in the nitrogen atmosphere at room temperature is as follows: Figure 6 As shown in the double logarithmic graph, it is worth noting that the burning rate of the catalyst-free H0 propellant at 1 MPa is much lower than that of the propellants with NHN and NHA added (H1 and H3). In particular, the burning rate of H3 at 1 MPa is 5.26 mm·s -1, which is 2.3 times higher than that of H0 propellant at this pressure. For H1 at 1MPa, the burning rate is 4.79mm·s -1 , 2.1 times higher than H0 propellant. This shows that the combustion catalytic effect of NHN and NHA at a content of 1% is the best.

[0066] At the same time, the pressure index (n) value of H3 has increased to 0.308, indicating that its burning rate is affected by pressure, but it meets the requirements of practical applications. Compared with other formulas, the pressure index of H3 has the smallest increase, which means that when the content of NHN and NHA increases, the effect of pressure on the burning rate of the propellant increases significantly.

[0067] 7. Propellant Flame Distribution

[0068] In order to further study the combustion performance of the prepared propellant, we used a high-speed infrared thermometer (Impac740) to record the flame temperature curve under 0.5MPa conditions, such as Figure 7 shown.

[0069] Since the infrared radiation rate of the propellant during combustion cannot be well determined in the experiment, and the experiment was carried out in a steel chamber without insulation treatment, there was a large heat loss, so the measured temperature was only compared horizontally. The results show that H3 has a higher combustion temperature of 2329.78℃. Compared with all the composite solid propellants, the higher combustion temperature of H3 reflects that the catalytic effect of NHA on the propellant is the best at a content of 1%.

[0070] 8. Analysis of Condensed Combustion Products (CCPs)

[0071] The concentrated combustion products were collected by bomb calorimetry after the explosion heat experiment and characterized by X-ray diffraction and laser particle analysis.

[0072] 1. Particle size and morphology of CCPs

[0073] The combustion efficiency of aluminum in propellants is very important, which corresponds to its agglomeration process. In order to evaluate the effects of NHN and NHA on the combustion behavior of aluminum, we further studied the collected condensed combustion products (CCPs) produced at 0.5 MPa. The SEM images of the CCPs of these propellants are shown in Figure 2. Figure 8 As shown, their differences in agglomeration extension and morphology are clearly shown.

[0074] Laser particle size distribution measurements were performed to elucidate the effect of NHN on the particle size of CCPs. The main reason for the formation of large-sized agglomerates in CCPs is the agglomeration of aluminum particles on the combustion surface. During the combustion of the propellant, the aluminum particles in the polymer matrix are exposed to the outside and heated to a molten state. Due to the influence of surface tension, part of the aluminum is retained on the combustion surface and then aggregates together. Finally, through the lift of the airflow, they will leave the combustion surface and enter the gas phase. There are many factors that affect aluminum agglomeration, including formulation, pressure, combustion rate, size and content of Al and AP, etc.

[0075] like Figure 8 As shown in the figure, the average CCPs size of H0 (a3) ​​is 23.89 μm, which is the largest among the three samples. With the addition of micron NHN, the average particle size of CCPs decreases to 18.44 (b3) and 13.89 μm (c3), respectively. At the same time, the CCPs of H1 and H2 are both less than 20 μm, indicating that NHN can better inhibit the agglomeration of Al particles. The CCPs size distribution of H2 is comparable to that of H3. The results show that NHN is effective in inhibiting the aggregation of Al particles in CCPs.

[0076] Similarly, the particle size of CCPs in formulas H3 and H4 with NHA added was further reduced, with the average particle size of H3 reduced to 11.28 μm, indicating that 1% NHA has the best catalytic effect on composite propellants among all formulas and contents.

[0077] 2. Chemical structure and phase composition of CCPs

[0078] X-ray diffraction (XRD) was also used to characterize CCPs, such as Fig. 9 As shown. The most abundant component in CCPs is Al. In addition, alumina, Al2OC and Al5O6N also exist in CCPs. Compared with the combustion products of H1, H2, H3, H4, H0, the Al diffraction peak of the combustion product of H0 is strong, which means that the Al reaction in H0 is incomplete. In H2, H3, H4, and H5 propellants, the characteristic peaks of alumina are generally stronger than those of H0, indicating that adding a catalyst can achieve higher combustion efficiency.

[0079] Through the above research and analysis of the thermal reactivity, burning rate, burning temperature and CCPs characteristics of HTPB-based composite solid propellants containing NHN or NHA, the following conclusions were drawn:

[0080] (1) The main exothermic decomposition peak temperatures of the propellants containing NHN or NHA are 353.74°C, 355.75°C, 350.45°C, and 347.45°C, which are 26.43°C, 24.36°C, 29.25°C, and 32.9°C higher than those of the propellants without NHN or NHA, indicating that NHA or NHN has good catalytic performance. Under the action of NHN or NHA, the DSC curves of H1, H2, H3, and H4 have no endothermic peaks, but have a narrow exothermic peak. According to the TGA curve, the mass loss of the composite propellants containing 1% and 5% NHA is the largest, reaching 85.31% and 81.9%, respectively, which indicates that the composite propellant with 1% NHA content has the best catalytic effect.

[0081] (2) The explosion heat of propellants containing NHN or NHA was higher than that of the blank addition group H0. Among them, the explosion heat of H3 was the highest, reaching 5744.98 J·g -1 , and it was proved that the catalytic effect of the two components at 1% content was the best.

[0082] (3) The burning rate of H3 at 1 MPa is 5.26 mm·s -1 , 2.3 times higher than H0. H3 can improve the combustion rate of the above CCPs in the low pressure range (<2MPa), and under this condition, it has a lower pressure index; the flame temperature of H3 is 631.62℃ higher than that of H0.

[0083] (4) After adding NHN, the average particle size of CCPs decreased from 23.89 μm to 18.44 μm and 13.89 μm, respectively. Compared with H0, the particle size decreased by 22.8% and 41.8%. After adding NHA, the average particle size of CCPs decreased to 11.28 μm and 14.06 μm, respectively. Compared with H0, the particle size decreased by 52.7% and 41.1%.

[0084] (5) The XRD results of H0 without catalyst show the strongest aluminum peak, which means slightly incomplete oxidation of aluminum, which is consistent with the lower flame temperature; for H1 and H2, the characteristic peaks of aluminum oxide are generally stronger than those of H0, indicating that the use of catalyst can lead to higher combustion efficiency.

[0085] In summary, among all the formulations, the composite propellant H3 (containing 1% NHA) has the best comprehensive performance and has broad application prospects in solid propellants.

[0086] The above content is a schematic description of the present invention and its implementation methods, which is not restrictive. What is shown in the embodiment is only one of the implementation methods of the present invention, and the actual implementation method is not limited thereto. Therefore, if a person of ordinary skill in the art is inspired by it and designs implementation methods and embodiments similar to the technical solution without creative design without departing from the purpose of the invention, they should all fall within the scope of protection of the present invention.

Claims

1. Use of [Ni(N2H4)3](NO3)2 and / or [Ni(N2H4)2](N3)2 in a solid propellant, the solid propellant comprising an oxidant, a reductant and an energetic catalyst; The energetic catalyst is Ni(N2H4)3](NO3)2 and / or [Ni(N2H4)2](N3)2, which is used to catalyze the combustion of the oxidizer in the solid propellant; The oxidizer is ammonium perchlorate, which accounts for 58% to 63% of the mass percentage of the solid propellant, excluding 63%; The mass percentage of the energetic catalyst in the solid propellant is 0-5%, excluding 0%; The reducing agent is aluminum powder, which accounts for 17% of the mass percentage of the solid propellant.

2. A solid propellant, characterized in that: It comprises an oxidant, a reductant and an energetic catalyst; the oxidant is ammonium perchlorate, and the energetic catalyst is [Ni(N2H4)3](NO3)2 and / or [Ni(N2H4)2](N3)2; The mass percentage of the oxidizer in the solid propellant is 58% to 63%, excluding 63%; the mass percentage of the energetic catalyst in the solid propellant is 0 to 5%, excluding 0%; The reducing agent is aluminum powder, which accounts for 17% of the mass percentage of the solid propellant.

3. The solid propellant according to claim 2, characterized in that: The sum of the mass percentages of the oxidant and the energetic catalyst accounts for 63% of the solid propellant.

4. The solid propellant according to claim 2 or 3, characterized in that: Also includes binders, plasticizers and curing agents.

5. The solid propellant according to claim 4, characterized in that: The adhesive includes hydroxyl-terminated polybutadiene HTPB, the plasticizer includes diisooctyl sebacate DOS, and the curing agent includes toluene 2,4-isocyanate TDI.

6. The method for producing a solid propellant according to any one of claims 4 or 5, characterized in that: The method comprises the steps of mixing and stirring an oxidant and an energetic catalyst.

7. The method for producing a solid propellant according to claim 6, characterized in that: Specifically including raw material drying, mixing, vacuum pouring and curing; Raw material drying: heat and dry the raw materials in a vacuum oven; Stirring: Add the adhesive, oxidant, plasticizer, energetic catalyst and curing agent into the container in sequence and mix them evenly in a vacuum stirrer; Vacuum casting: The slurry is poured into a PTFE mold and maintained under high vacuum; Curing: Place the mold in an oven and heat it to obtain a fully cured solid propellant.

Citation Information

Patent Citations

  • Process for preparing nickel hydrazine nitrate

    CN1042625C

  • Smokeless propellant powder with safe, environmental-friendly and porous structure for fireworks

    CN102924193A